ARTICLES IN THE NOVEL „BLACK BOOK“ BY ORHAN PAMUK AND THEIR TRANSLATION EQUIVALENTS IN THE TRANSLATION OF ILHAMI EMIN - Minova, Despina (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
In the novel “Black book“ (“Kara Kitap") by Orhan Pamuk, one of the most known Turkish authors of today, all types of articles in Turkish language have been used. This novel in Macedonian is translated by Ilhami Emin. In his translation into Macedonian, Emin successfully used different translation equivalents. When comparing the articles in the original work in the Turkish language and the translated articles in Macedonian, we can see the rich vocabulary in both languages.